Influence of nicotine on choline-deficient, L-amino acid-defined diet-induced non-alcoholic steatohepatitis in rats. - Hiroyuki Kanamori; Yukiomi Nakade; Taeko Yamauchi; Kazumasa Sakamoto; Tadahisa Inoue; Takaya Yamamoto; Yuji Kobayashi; Norimitsu Ishii; Tomohiko Ohashi; Kiyoaki Ito; Yoshio Sumida; Haruhisa Nakao; et al. (PLoS ONE)
Nicotine, a major compound in cigarette smoke, decreases food intake and body weight gain in mammals; however, the influence of nicotine on the progression of non-alcoholic steatohepatitis (NASH) remains controversial. This study aimed to investigate the effect of nicotine on NASH in rat models. Male Wistar rats were fed choline-deficient, l-amino acid-defined (CDAA) diet and treated with nicotine or saline. Food intake, body weight gain, presence of hepatic steatosis, inflammation, and fibrosis were assessed 6 weeks after the rats were fed CDAA diet. Hepatic branch vagotomy was performed to elucidate the mechanism through which nicotine affected steatohepatitis. CDAA diet induced hepatic steatosis, inflammation, and fibrosis, as well as increased the expression of inflammation-related genes. Conversely, nicotine significantly attenuated food intake, body weight gain, and inhibited the CDAA-diet-induced hepatic steatosis, inflammation, and fibrosis, together with increased expression of inflammation-related genes. Hepatic branch vagotomy by itself decreased food intake, body weight gain, and attenuated the CDAA-diet-induced hepatic steatosis, but not inflammation. However, nicotine did not change the food intake, body weight gain, and CDAA diet-induced hepatic steatosis and inflammation in vagotomized rats. These results suggest that nicotine attenuates the CDAA-diet-induced hepatic steatosis and inflammation through the hepatic branch of the vagus nerve in rats.